2009
DOI: 10.1254/jphs.08249fp
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Benzodiazepine-Receptor Agonists on Buprenorphine-Induced μ-Opioid Receptor Regulation

Abstract: Abstract. In this study, we compared the effects of five short-, medium-, or long-acting benzodiazepine-receptor agonists (BZDs) [alprazolam (APZ), clonazepam (CLZ), flunitrazepam (FLZ), loprazolam (LPZ), zolpidem (ZLP)], at two distinct doses, 0.2 and 2 mg/kg, on the cell surface regulation of μ-opioid receptor induced by 0.15 mg/kg buprenorphine (BPN) in specific regions of the rat brain. Using 0.312 -5 nM [ 3 H]-DAMGO concentrations and Scatchard plot analysis, B max (maximal receptor density) and K d (diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
(35 reference statements)
0
20
1
Order By: Relevance
“…Moreover, Poisnel et al. suggested that benzodiazepines, concurrently administered with methadone to opioid addicts, induce μ‐receptor up‐regulation and increase recruitment of receptors allowing μ‐ligands greater accessibility, and this co‐administration may result in lethal respiratory depression . However, in contrast to the findings of Mikoalenko and Poisnel in cases of co‐intoxication with benzodiazepines, we (and other authors, too) did not find higher concentrations of methadone, when compared to cases of methadone toxicity alone .…”
Section: Discussioncontrasting
confidence: 93%
“…Moreover, Poisnel et al. suggested that benzodiazepines, concurrently administered with methadone to opioid addicts, induce μ‐receptor up‐regulation and increase recruitment of receptors allowing μ‐ligands greater accessibility, and this co‐administration may result in lethal respiratory depression . However, in contrast to the findings of Mikoalenko and Poisnel in cases of co‐intoxication with benzodiazepines, we (and other authors, too) did not find higher concentrations of methadone, when compared to cases of methadone toxicity alone .…”
Section: Discussioncontrasting
confidence: 93%
“…FLZ that is widely abused and augments buprenorphine toxicity appeared the most potent to increase mu-cell surface receptor density at the lowest dose of 0.2 mg/kg. Among people using buprenorphine and benzodiazepines, the effects described here are likely to influence addictive behaviors and induce toxic effects that could be quantitatively different due to the quality of the benzodiazepines (Poisnel et al, 2009). …”
Section: A Caution About Toxicitymentioning
confidence: 99%
“…36 Sedative hypnotic drugs act synergistically with opioids by acting on receptors and channels distinct from mu opioid receptors. [37][38][39] Patients with underlying medical conditions, including obstructive sleep apnea and chronic obstructive pulmonary disease, also predispose to carbon dioxide retention, thereby placing these patients in an unfortunate positive feedback loop when opioids are administered to them at inappropriate doses or intervals. 20,40,41 Patients 2, 4, and 5 emphasize these principles.…”
Section: Drug-drug Drug-disease Synergymentioning
confidence: 99%
“…Similarly, in patient 5, the benzodiazepine receptor agonist, zolpidem, which has been documented to augment the respiratory depressant effect of opioids, 39 was administered midway between the dosing of 11 mg of intravenous hydromorphone given over an interval of 6 hours.…”
Section: Drug-drug Drug-disease Synergymentioning
confidence: 99%